Reconfigurable photothermal doping filament for selective spin manipulation and addressing - Zhi-Wei Liu; Meng-Qi Ma; Bo-Wen Sun; Liang Li; Wang Jiang; Han-Xiang Zang; Zhe Bai; Yang Dong; Shao-Chun Zhang; Xiang-Dong Chen; Chong-Wen Zou; Guang-Can Guo; et al. (Proceedings of the National Academy of Sciences, 2025)
The room temperature manipulation of solid-state spins provides an opportunity to develop quantum applications under ambient conditions. Local electromagnetic fields, that usually produced by current in micro/nanoscale metal wires, have been employed for the coherent driving and addressing of spin qubit. However, the fixed distribution limits the spatial selectivity and efficiency of qubit manipulation, which is of central importance in a scaled-up quantum system. Here, we report a solution by demonstrating a reconfigurable current with arbitrary shape to engineer microwave and DC magnetic field at microscale. A “photothermal doping” method was proposed to optically control local insulator-to-metal transition in vanadium dioxide. It generates a conducting filament with adjustable position, direction, and width. Universal manipulation and selective addressing of spins at arbitrary sites are realized, by freely changing the filament and electromagnetic field on demand. Our work paves the way for developing quantum devices with large-scale spin qubits.